Calculation of the Exchange Fund of Electrical Equipment of Industrial Enterprises - Basmanov V.G.; Kholmanskikh V.M.; Cherepanov V.V.; Ozhegov A.N.,; Zakalata A.A. (Problems of the Regional Energetics)
The purpose of this work is the theoretical substantiation and development of a practical method for calculating the exchange fund of electrical equipment of an industrial enterprise. The purpose is achieved through the use of separate methods of queuing theory if the flow of applications for repairs and restoration are the simplest. It is confirmed by the results of statistical studies. Therefore, for the mathematical description of the repair problem the authors use the scheme Mm; Ms; n , which corresponds to the process of death and reproduction. As a criterion for optimizing the exchange fund of electrical equipment it is proposed to use the zero probability waiting for the replacement of a faulty electrical component with a working from the exchange fund. For the case of the simplest flow of applications for service, the authors suggest to use the Peck and Hazelwood tables, which significantly simplify the calculation of the exchange fund for known failure rates and electrical equipment recoveries. For practical use of the proposed method, the authors have developed convenient forms for presenting initial data for calculating the exchange fund, and it is proposed to present the results of calculations in the form of several options for the optimal number of electrical equipment in the exchange fund depending on the accepted level of zero expectation probability, the number of elements from the exchange fund and their recovery time. The proposed method will optimize the exchange fund of electrical equipment and reduce the cost of its formation.